Undergraduate ESL students' difficulties in writing the introduction for research reports - Maznun, Mirrah Diyana; Monsefi, Roya; Nimehchisalem, Vahid (Australian International Academic Centre, 2017)
This study was conducted to investigate the difficulties encountered by undergraduate ESL students in writing the introduction section of their project reports. Five introduction sections of bachelor of arts students, majoring in English language, were analyzed and a lecturer was interviewed regarding the areas of the students' weaknesses. Swales' create-a-research-space (cars) model was used as the analytical framework of the study. The results revealed that students confronted problems in writing their introduction for each move especially for move 2, which consists of counter claiming, indicating research gap, raising questions from previous research and continuing tradition. It was also found that the students had difficulty in writing the background of the study, theoretical framework, and statement of the problem which indicated their unawareness of the appropriate rhetorical structure of the introduction section.